PENGEMBANGAN BUKU PENGAYAAN FISIKA TERINTEGRASI ETNOPHYSICS PADA ALAT MUSIK GENDANG MELAYU JAMBI BERBANTUAN HEYZINE FLIPBOOK DAN APLIKASI PHYPHOX - Helmalia Putri Hasibuan, Linda; Jufrida; Shidow Falah, Hebat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an integrated physics enrichment book on ethnophysics using the traditional Jambi Malay drum (Gendang Melayu Jambi) as a subject. The method used was Research and Development (R&D) with a 4D development model comprising the define, design, development, and disseminate stages. The results showed that in the initial validation stage, the enrichment book received a score of 66.84% from subject matter experts and 69.53% from media experts, both in the “good” category. After revisions were made, the validation results increased to 85.46% and 86.20%, both in the “very good” category. A pilot test involving 36 students showed a positive response to the developed book. Thus, the ethnophysics-based enrichment book on the Gendang Melayu Jambi is suitable for use as supplementary teaching material in physics education.